Relationship of deviant behavior and value orientations of athletes from the sports reserve - Skok N.S.; Makarov Yu.M.; Kulikov V.S.; Ulitskaya T.I.; Chernaya A.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between deviant behavior and value orientations of athletes from the sports reserve. Methods and structure of the study. Pedagogical experiment, sociological research (distribution survey) in sports schools in St. Petersburg (November 2022 - August 2023), correlation analysis, analysis and generalization of research results. Results and conclusions. A predisposition to socially determined behavior was established in a significant part of the subjects, as well as a situational predisposition to dependent, aggressive and self-harming behavior. A relationship has been identified between a predisposition to various manifestations of deviant behavior and the value orientations of athletes from the sports reserve. The recorded relationships show the existing contradictions between the presence of positive life guidelines and non-normative ways of achieving them, and also reveal the lack of formed socially approved models of behavior to achieve set goals, which leads to manifestations of deviant behavior of athletes from among the sports reserve.